Acoustic properties of two parallel elastic plates - WESOŁOWSKI, Zbigniew (Archives of Acoustics, 2015)
Two parallel elastic plates are submerget in gas. A plane sinusoidal wave propagates perpendicularily to the plates. Such a system models a paned window. In order to present the physical phenomenon without excessively developing the mathematical description, the plates are modelled by rigid plane screens suspended elastically. The displacement of the screen is proportional to the force, and the suspension rigidity is proportional to the third power of the screen thickness (as in a bonded plate). On the basis of motion equations and continuity equations, the displacement behind both plates is determined. The attenuation coefficient depends on the frequency, plate thickness and their spacing. Plates with different thicknesses give a better characteristic than those with identical thicknesses. The attenuation coefficient does not depend on the sequence of plates and it has two maximum in the acoustical range. Frequencies corresponding to them differ from the frequencies of free vibrations of the plates and the cavity.